Unexpected field-induced dynamics in magnetostrictive microstructured elements under isotropic strain. (10th July 2018) - Finizio, Simone; Wintz, Sebastian; Gliga, Sebastian; Kirk, Eugenie; Suszka, Anna Kinga; Wohlhüter, Phillip; Zeissler, Katharina; Raabe, Jörg
Abstract: We investigated the influence of an isotropic strain on the magnetization dynamics of microstructured magnetostrictive Co40 Fe40 B20 (CoFeB) elements with time-resolved scanning transmission x-ray microscopy. We observed that the application of isotropic strain leads to changes in the behavior of the microstructured magnetostrictive elements that cannot be fully explained by the volume magnetostriction term. Therefore, our results prompt for an alternative explanation to the current models used for the interpretation of the influence of mechanical strain on the dynamical processes of magnetostrictive materials.